Interventional Ultrasound for Ovarian Cyst Aspiration During Pregnancy; A Case Report and Literature Review - Abdelkhair, Sami M; Ahmed, A.Ashmaig Badreldeen; Miskeen, Elhadi (مجلة الجزيرة للعلوم الصحية; مجلد 12 عدد 1 (2016), 2016)
Abstract: Herewith we present perinatal outcome in pregnancies with ovarian cysts after fine needle aspiration in the second trimester and excision during c-section at term. Outcome was satisfactory for both maternal and fetal. 28 years primigravida presented with huge ovarian cyst, size 18 X 16 cm in her second trimester of pregnancy. The procedure was performed without anaesthesia under ultrasound guidance. Three litres were aspirated within two hours while the patient was on her right lateral position. Cytology of the aspirated fluid revealed a simple ovarian cyst and no evidence of malignancy. The pregnancy continued uneventfully. C-section was done at 37 weeks gestational age.  Ovarian cystectomy was performed. The result of histopathology was benign cystadenoma. We concluded that ovarian cyst aspiration under ultrasound guidance is simple, safe and useful in the management of ultrasonically benign ovarian cysts. We advocate using this procedure in similar situation and same characteristics.